Influences of Ti additions on the microstructure and tensile properties of AlCoCrFeNi2.1 eutectic high entropy alloy. (January 2021) - Chen, Xiaohua; Xie, Weiyang; Zhu, Jin; Wang, Zidong; Wang, Yanlin; Ma, Yifei; Yang, Ming; Jiang, Wenwen; Yu, Huiwen; Wu, Yidong; Hui, Xidong
Abstract: Tix AlCoCrFeNi2.1 (x = 0, 0.1, 0.15, 0.2) high entropy alloys (HEAs) were obtained by vacuum arc melting followed by suction casting. The influences of traces of Ti addition on the microstructure morphology, average phase fraction, phase orientation relationship (OR) were investigated employing X-ray diffraction (XRD), scanning electron microscopy (SEM) equipped with energy-dispersive spectroscopy (EDS), electron-probe microanalyzer (EPMA), electron back-scattered diffraction (EBSD), transmission electron microscope (TEM). Tensile tests were conducted. Results reveal that microstructures show a morphology transition from lamellae to petal after adjunction of Ti, forming a dual phase of L12 and B2. Strict K–S OR, namely, {111}FCC //{011}B2, <011>FCC //<111>B2 between lamellar microstructure has been verified, while the petal-like microstructure deviates from such OR. Cr-rich nano-particles with different morphologies inside the B2 phase are coherent with B2 matrix for Ti0.15 AlCoCrFeNi2.1 alloy. With the increase of Ti content, ultimate tensile strength (UTS) and elongation increase firstly and subsequently decrease till with 3.17 at.% (x = 0.2) Ti addition. The as-cast Ti0.15 AlCoCrFeNi2.1 alloy exhibits a well combination of UTS (1253 MPa) and acceptable ductility (12.9%), which can be attributed to the balance of L12 and B2 phases as well as the precipitation of Cr-rich nano-particles inside the B2 phase. Highlights: AlCoCrFeNi2.1 alloy was fabricated with Ti addition. Microstructures remain a dual phase of L12 and B2 regardless of Ti addition. Microstructures show a morphology transition from lamellar to petal. Ti0.15 AlCoCrFeNi2.1 alloy shows a well combination of strength and ductility.